(untitled) (Journal of Parents and Teachers, 2014)
Today we live in a society where information is at our fingertips just by making a query on the Internet. But the pages we consult are not always reliable and therefore this article gives some guidelines to teachers to do with their students to teach them to be critical of the sources they use.